Early palliative care in cancer patients - Jung Hye Kwon (Korean Journal of Clinical Oncology, 2014)
Cancer patients suffer from various co-existing symptoms which come from cancer, cancer related complications and treatment related side effects. Integrating early palliative care into standard oncology practice has been proven to improve quality of life of patients and caregivers as well as to prolong survival of patients. However, there have been barriers to spreading early palliative care including less established concept of palliative care, lack of palliative care specialist, and reimbursement issues. Support from national health care system is essential to establish early palliative care in oncology practice.